Child Ability and Household Human Capital Investment Decisions in Burkina Faso - Akresh, Richard; Bagby, Emilie; de Walque, Damien; Kazianga, Harounan (2012)
Using data they collected in rural Burkina Faso, the authors examine how children's cognitive abilities influence resource constrained households' decisions to invest in their education. This paper uses a direct measure of child ability for all primary school-aged children, regardless of current school enrollment. The analysis explicitly incorporates direct measures of the ability of each child s siblings (both absolute and relative measures) to show how sibling rivalry exerts an impact on the parents decision of whether and how much to invest in their child s education. The findings indicate that children with one standard deviation higher own ability are 16 percent more likely to be currently enrolled, while having a higher ability sibling lowers current enrollment by 16 percent and having two higher ability siblings lowers enrollment by 30 percent. The results are robust to addressing the potential reverse causality of schooling influencing child ability measures and using alternative cognitive tests to measure ability.